Project-Based Learning Media: Embossed Maps of Social Studies Material Content - I Putu Yogi Pratama Putra; I Wayan Sujana; Ni Nyoman Ganing (Jurnal Pendidikan dan Pengajaran, 2024)
The lack of use of learning media in learning poses and the lack of visual learning media thus affecting the low level of interaction and attention of learners to teaching and learning activities. This study aims to determine the design, feasibility of media, and effectiveness of embossed map media. This research is development research applying the ADDIE model. The data collection method uses observation, interviews, questionnaires, and tutorials of the work. Data analysis uses quantitative descriptive, qualitative descriptive, and inferential statistics. The results of the media were obtained to have validity from the test results of design experts 87.5%, learning material experts 90%, learning design experts 87.5%, learning media experts 88.63%, individual trials 90%, small group trials 91.6%, and field trials of 88.6%. The result of the t-test obtained tcount (11.368) is greater than ttable (2.262) so that H1 is accepted. It can be concluded that embossed map media has proven feasible and effective to be applied to class V social studies subjects.